Characterization of a highly pathogenic Bacillus thuringiensis strain isolated from common cockchafer, Melolontha melolontha - Kati, H; Sezen, K; Demirbağ, Z (Folia microbiologica, 2007)
A bacterial isolate (Mm2) of Melolontha melolontha was identified and characterized. Based on various morphological, physiological, biochemical and molecular characteristics, it was identified as Bacillus thuringiensis subsp. tenebrionis. This isolate was compared to the reference strains by electron microscopy, SDS-PAGE analysis, plasmid pattern, cry gene content and insecticidal activity. Cells of the isolate harbored flat square inclusions containing a protein component of approximately equal to65 kDa. After trypsin digestion of solubilized crystals, SDS-PAGE resolved a unique proteinase-resistant peptide of approximately equal to 50 kDa. Plasmid pattern showed similar bands to those of the reference strain, PCR analysis showed that the isolate has cry3 gene. Toxicity tests (against 5 coleopteran species) showed 80 % insecticidal activity against the larvae of M. melolontha. The isolate Mm2 may be valuable as biological control agent for M. melolontha and other coleopteran insects.
Keywords: druhová specificita; Genes, Bacterial; molekulová hmotnost; biologická kontrola škůdců; hemolyziny; zvířata; buněčná inkluze; bakteriální proteiny; Coleoptera; Endotoxins; Hemolysin Proteins; Bacillus thuringiensis Toxins; Bacterial Toxins; Bacillus thuringiensis; bakteriální geny; toxiny Bacillus thuringensis; endotoxiny; Inclusion Bodies; Pest Control, Biological; Species Specificity; Bacterial Proteins; brouci; Animals; bakteriální toxiny; Molecular Weight